Особливості професійних моральних якостей курсантів закладів вищої освіти МВС України - Маравська, К. І.; Maravska, K. I.; ORCID: http://orcid.org/0000-0002-7103-4350 (Право і безпека. – 2018. – № 4 (71). – С. 104-110, 2018)
Розглянуто особливості професійних моральних якостей курсантів закладів вищої освіти МВС України різної статі та різних років навчання, а також умови їх формування. За допомогою опитувальника визначено рівні розвитку моральних якостей курсантів Харківського національного університету внутрішніх справ за такими категоріями, як ставлення до Батьківщини, ставлення до суспільства, ставлення до службової діяльності, ставлення до інших і до себе, а також загальний рівень моральних особистісних якостей. Надано пропозиції щодо вдосконалення процесу підготовки курсантів.

The results of empirical research of professional moral qualities of cadets of the institutions of higher education of the Ministry of Internal Affairs of Ukraine in the context of specific features of their development have been considered. It has been emphasized that the problem of development of moral qualities of cadets is stipulated by the high level of requirements to general, professional and moral qualities of police officers, the need to take into account them within professional and psychological selection of candidates for the positions of police officers and to form them in the educational process in the institutions of higher education of the Ministry of Internal Affairs of Ukraine. This problem is complex, especially relevant in the context of the development of professional legal awareness and the culture of law enforcement officers at the stage of training in higher educational institutions. It has been noted that the development of moral qualities of cadets occurs as a result of their understanding of moral norms that exist in society, in particular in the professional environment, their critical thinking, internalization. The process of development of professional moral qualities of future police officers is realized in the system of training and educational process in institutions of higher education, the conditions of which are aimed at adequate assimilation of professional and moral requirements. The author has provided the results of the research, which included 168 cadets of different gender of Kharkiv National University of Internal Affairs. Using the questionnaire “The moral profile of personality”, developed by A. A. Tokman, the author has determined the levels of development of moral qualities of cadets according to such categories as: the attitude to the Motherland, attitude to society, attitude to the official activity, attitude to others and to oneself, and also to the general level of moral personal qualities. It has been determined that the level of development of moral qualities of cadets on the majority of scales of the questionnaire is low. It has been found out that cadets of the fourth year of study, become more demanding for themselves and their own disadvantages, they seek self-improvement. In general, the author has defined that there is a positive tendency for the development of professional moral qualities of those being studied. On the basis of the empirical research, the author has provided propositions related to the improvement of the training process of cadets.

Рассмотрены особенности профессиональных моральных качеств курсантов заведений высшего образования МВД Украины разного пола и разных лет обучения, а також условия их формирования. С помощью опросника определены уровни развития моральных качеств курсантов Харьковского национального университету внутренних дел по таким категориям, как отношение к Родине, отношение к обществу, отношение к служебной деятельности, отношение к другим и к себе, а также общий уровень моральных личностных качеств. Даны предложения по совершенствованию процесса подготовки курсантов.
Specific features of professional moral qualities of cadets of the institutions of higher education of the Ministry of Internal Affairs of Ukraine
Особенности профессиональных моральных качеств курсантов заведений высшего образования МВД Украины
Маравська, К. І. Особливості професійних моральних якостей курсантів закладів вищої освіти МВС України / Катерина Ігорівна Маравська // Право і безпека. – 2018. – № 4 (71). – С. 104-110. – DOI: https://doi.org/10.32631/pb.2018.4.15.
Maravska, K. (2018) Особливості професійних моральних якостей курсантів закладів вищої освіти МВС України, Право і безпека, 71(4), pp 104-110. doi: 10.32631/pb.2018.4.15.
Keywords: Психологія. Рsychology. Психология; Освіта. Педагогіка. Education. Pedagogy. Образование. Педагогика; Державне адміністративне управління. Адміністративна діяльність. State Administration. Administrative Activity. Государственное административное управление. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; моральні якості; рівень розвитку; курсанти; поліцейський; Харківський національний університет внутрішніх справ; заклади вищої освіти Міністерства внутрішніх справ України; moral qualities; level of development; cadets; police officers; institution of higher education of the Ministry of Internal Affairs of Ukraine; Kharkiv National University of Internal Affairs; моральные качества; уровень развития; курсанты; полицейский; Харьковский национальный университет внутренних дел; заведения высшего образования Министерства внутренних дел Украины